Some properties of the nilradical and non-nilradical graphs over finite commutative ring Zn - Chandra, S.; Prakash, O.; Suthar, S. (Algebra and Discrete Mathematics, 2017)
Let Zn be the finite commutative ring of residue classes modulo n with identity and Γ(Zn) be its zero-divisor graph. In this paper, we investigated some properties of nilradical graph, denoted by N(Zn) and non-nilradical graph, denoted by Ω(Zn) of Γ(Zn). In particular, we determined the Chromatic number and Energy of N(Zn) and Ω(Zn) for a positive integer n. In addition, we have found the conditions in which N(Zn) and Ω(Zn) graphs are planar. We have also given MATLAB coding of our calculations.